On Characterization of Gompertz Distribution by Properties of Generalized Record Values - S. Minimol (Journal of Statistical Theory and Applications (JSTA), 2014)
In this chapter, we derive some recurrence relations satisfied by single and product moments of generalized record values arising from Gompertz and inverted Gompertz distributions. Further, we have obtained characterization of Gompertz and inverted Gompertz distributions based on certain properties of generalized record values.